KONTRIBUSI KEKUATAN OTOT LENGAN DAN KEKUATAN OTOT PUNGGUNG TERHADAP BANTINGAN LENGAN PADA ATLET GULAT PPLP DISPORA RIAU - Devi Mayasari; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The study was carried out using a correlational research design that aims to determine how much the contribution between the independent variables namely arm muscle force (X1) and back muscle force (X2) to the dependent variable, namely the capacity of the kick arm (Y), the population in this study all research objects, namely PPLP Riau wrestles athletes as many as 10 people. Based on the results of the research described by the author in the previous chapter, it can be concluded that there is a significant relationship between arm muscle strength and arm slamming, where r count (0.979)> rtab (0.666), with a contribution of 94.09 %. Then there is a significant relationship between the strength of the back muscles and the ability to kick against the arm, where r count (0.819)> rtab (0.666), with a contribution of 65.61%. There is a joint relationship between arm muscle strength and back muscle strength with the capacity of the arm kick with a significant level α (0.05) = 0.666 means, r count (0.982)> rtab (0.666) with a contribution of 96.43%.Key Words: Arm Muscles And Back Muscle Strength Against Arm Prints